Efektivitas Penerapan Tilang Elektronik terhadap Penindakan dan Pencegahan Pelanggaran Lalu Lintas di Direktorat Lalu Lintas Polda Metro Jaya - Dessica Dwiyuliana; Mohammad Yani; Anang Sunardi; Ernawati Mursalim; Renie Dwi Sulistyani; Hamka Hamka (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This examination is persuaded by the ineffectiveness of the ticketing process using a ticket blank by the Ditlantas officer unit of the Polda Metro Jaya in tackling traffic violators. For this reason, the Polda Metro Jaya Traffic Directorate uses a new program issued by the National Police Korlantas, namely E-tickets. This e-ticket program has been operating since December 16, 2016. However, in the implementation of the ticketing process using e-tickets, it is still not optimal and not as expected. Hence, a review was directed that aims to determine the description of the use of e-tlang by Ditlantas Polda Metro Jaya officers, the factors that hinder the application of e-tickets. This exploration was directed utilizing a subjective methodology utilizing illustrative examination strategies, as well as information assortment procedures by interviewing, observing and reviewing documents. The aftereffects of the investigation discovered that the utilization of e-tickets was still not ideal. This is because of a few variables, to be specific 1) Legal Substance Factors 2) Law Enforcement Factors. 3) Factors of Facilities or Facilities. 4) Factors of Community Legal Culture. 5) Natural or Environmental Factors. In light of the aftereffects of the examination above, it very well may be presumed that the utilization of e-tickets by Ditlantas Polda Metro Jaya officers has not been effective. Implementation in the field is still experiencing obstacles, both officers and the environment. In response to this, the Ditlantas Polda Metro Jaya has made efforts to increase the effectiveness of prosecution and prevention of criminal traffic offenses.